The humanitarian flying warehouse. (April 2020) - Jeong, Ho Young; Yu, David J.; Min, Byung-Cheol; Lee, Seokcheon
Highlights: Proof-of-concept study for HFW system in conflict zones. Multi-objectives model with the consideration of humanitarian principles. Epsilon-constraint method is used to address conflicting objectives. The model is applied to the case study based on northeast Syria. Comparative analysis between HFW system and ground-based UAVs system. Abstract: Delivering commodities by ground vehicles to people in conflict zones risks the safety of humanitarian aid workers. Hundreds of aid workers are killed, injured, or kidnapped when delivering supplies on the road each year. We propose the humanitarian flying warehouse (HFW) as a solution to these issues. The HFW is an airship that stays at high altitudes and uses unmanned aerial vehicles (UAVs) to deliver supplies. This innovation will enable safe and timely delivery to hard-to-reach populations in a manner that significantly exceeds the capacity of current practices. Crucially, the HFW eliminates the motivations behind many delivery disruptions. These disruptions are caused by asymmetric commons dilemmas: entities with different accessibility and power race to grab shared relief goods before others. The problem we address is the operation of HFW to make safe and timely delivery of critical items such as health supplies to the hard to reach populations. This study constitutes proof of concept for the HFW system in conflict zones through a multi-objective mathematical model. The validity of the system is verified via comparative analysis with a ground-based system in a realistic case study.